Epidemiological Evidence for Associations Between Genetic Variants and Osteosarcoma Susceptibility: A Meta-Analysis - Yuan, Dechao; Tian, Jie; Fang, Xiang; Xiong, Yan; Banskota, Nishant; Kuang, Fuguo; Zhang, Wenli; Duan, Hong (Frontiers in Oncology, 2022)
Background: Previous studies have proved that single nucleotide polymorphisms (SNPs) might be implicated in the pathogenesis of osteosarcoma (OS). Numerous studies involving SNPs with OS risk have been reported, these results, however, remain controversial and no comprehensive research synopsis has been performed till now. Objective: To clarify the relationships between SNPs and OS risk using a comprehensive meta-analysis, assess epidemiological evidence of significant associations. Methods: The PubMed, Web of Science, and Medline were used to screen the articles that evaluated the association between SNP and OS susceptibility in humans before 24 December 2021. Furthermore, we used Venice criteria and a false positive report probability (FPRP) test to assess the grades of epidemiological evidence for the statistical relationships. Results: We extracted useful data based on 43 articles, including 10,255 cases and 13,733 controls. Our results presented that 25 SNPs in 17 genes were significantly associated with OS risk. Finally, we graded strong evidence for 17 SNPs in 14 genes with OS risk (APE1 rs1760944, BCAS1 rs3787547, CTLA4 rs231775, ERCC3 rs4150506, HOTAIR rs7958904, IL6 rs1800795, IL8 rs4073, MTAP rs7023329 and rs7027989, PRKCG rs454006, RECQL5 rs820196, TP53 rs1042522, VEGF rs3025039, rs699947 and rs2010963, VMP1 rs1295925, XRCC3 rs861539), moderate for 14 SNPs in 12 genes and weak for 14 SNPs in 11 genes. Conclusion: In summary, this study offered a comprehensive meta-analysis between SNPs and OS susceptibility, then evaluated the credibility of statistical relationships, and provided useful information to identify the appropriate candidate SNPs and design future studies to evaluate SNP factors for OS risk.